2001
DOI: 10.1210/jcem.86.1.7157
|View full text |Cite
|
Sign up to set email alerts
|

Rosiglitazone Monotherapy Is Effective in Patients with Type 2 Diabetes

Abstract: This study evaluated the efficacy and safety of rosiglitazone monotherapy in patients with type 2 diabetes. After a 4-week placebo run-in period, 493 patients with type 2 diabetes were randomized to receive rosiglitazone [2 or 4 mg twice daily (bd)] or placebo for 26 weeks. The primary end point was change in hemoglobin A 1c ; other variables assessed included fasting plasma glucose, fructosamine, endogenous insulin secretion, urinary albumin excretion, serum lipids, and adverse events. Rosiglitazone (2 and 4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

11
161
2
5

Year Published

2003
2003
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 380 publications
(184 citation statements)
references
References 52 publications
11
161
2
5
Order By: Relevance
“…In adipose tissue, the resulting increase of fatty acid re-esterification would be facilitated by the concomitant increase of proteins that allow their uptake and acyl-CoA activation, as expected from the reported increase in the corresponding mRNAs by PPAR␥ agonists (10,24). Furthermore, it was observed that a 6-month rosiglitazone monotherapy in patients with type 2 diabetes enhances the body weight, although moderately (25).…”
Section: Discussionmentioning
confidence: 80%
“…In adipose tissue, the resulting increase of fatty acid re-esterification would be facilitated by the concomitant increase of proteins that allow their uptake and acyl-CoA activation, as expected from the reported increase in the corresponding mRNAs by PPAR␥ agonists (10,24). Furthermore, it was observed that a 6-month rosiglitazone monotherapy in patients with type 2 diabetes enhances the body weight, although moderately (25).…”
Section: Discussionmentioning
confidence: 80%
“…Peroxisome proliferator-activated receptor ␥ (PPAR␥) 5 is a nuclear receptor whose activation by thiazolidinediones (TZDs) effectively improves systemic insulin sensitivity and lowers plasma glucose levels in both human patients and rodent models of type 2 diabetes (1)(2)(3)(4)(5)(6)(7)(8). Because TZDs are effective in liver-or muscle-specific PPAR␥-deficient mice (9, 10) but not in adipose tissue-deleted mice (11) and adipose-specific PPAR␥-deficient mice (12), adipose tissue has been considered as the primary target site for the anti-diabetic effect of PPAR␥ activation (13,14).…”
mentioning
confidence: 99%
“…5,6) TZDs are reported to influence several processes that increase cell sensitivity to insulin, 7,8) including activation of peroxisome proliferator-activated receptor g (PPARg), 9,10) although their mechanism has not been fully elucidated. TZDs are widely used in clinical practice, but in some cases they cause weight gain, plasma volume expansion, edema or hepatotoxicity.…”
mentioning
confidence: 99%